Application of systems approach at early stages of designinng unmanned towed underwater systems for shallow water areas - Blintsov, Volodymyr; Kucenko, Pavel (Eastern-European Journal of Enterprise Technologies, 2019)
Typical configuration of an unmanned towed underwater system (UTUS) was described and advantages of using this type of marine equipment for shallow depth works were outlined. A list of basic operating modes of the UTUS which are key modes for design calculations of the system was determined. Basic requirements to the design and construction of a competitive UTUS for shallow water areas have been formed. The main requirements include the need for high-performance underwater technologies and the use of state-of-the-art computer research and design software. The need to maximize use of materials, parts and units that are commercially available as components for the UTUS was also indicated. Expediency and possibility of applying the systems approach methodology at early stages of the UTUS design were shown. Equations of existence were formulated in a matrix form for the UTUS components which make it possible to check engineering solutions for compliance with the requirements of the Requirements Specification already at the stages of technical proposal and sketch design. Structural, power, information and operational characteristics of the UTUS components were used as the compliance criteria. Sequence of the design works was completed in a form of a generalized design algorithm that implements the systems approach using modern computer technologies and equations of the UTUS existence. The developed algorithm allows the designer to check requirements of the Requirements Specification already at the early stages of the UTUS design and forms a scientifically substantiated methodological basis for creation of competitive underwater equipment